Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1097/00007890-200211150-00010
|View full text |Cite
|
Sign up to set email alerts
|

17??-Estradiol protects isolated human pancreatic islets against proinflammatory cytokine-induced cell death: molecular mechanisms and islet functionality1

Abstract: Estradiol promoted IHPI survival and improved functionality after PIC exposure in vitro and in vivo after transplantation. The molecular mechanisms involved included a decrease in NF-kappaB nuclear translocation, decrease in mitochondrial cytochrome release, and caspase 9 activation. The use of estradiol might be beneficial in clinical islet transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(67 citation statements)
references
References 29 publications
5
62
0
Order By: Relevance
“…This finding is important as apoptosis is known to play an important role in growth plate homeostasis . Although estrogen is well known to have antiapoptotic actions in other tissues (Contreras et al 2002, Rau et al 2003, it is not clear how estrogen affects chondrocyte cell death. Here, we demonstrate that the withdrawal of estrogen induces apoptosis in a caspasedependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is important as apoptosis is known to play an important role in growth plate homeostasis . Although estrogen is well known to have antiapoptotic actions in other tissues (Contreras et al 2002, Rau et al 2003, it is not clear how estrogen affects chondrocyte cell death. Here, we demonstrate that the withdrawal of estrogen induces apoptosis in a caspasedependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Estradiol also has a protective role for isolated human islets. It acts against pro-inflammatory cytokine-induced cell death by lowering NF-kappaB nuclear translocation, cytochrome release, and caspase-9 activation (Contreras et al, 2002a). Similarly, Giannoukakis et al (2000a) found that Fas-triggered apoptosis of human islets with IkappaB was inhibited following IkappaB alpha gene transfer.…”
Section: Increasing the Expression Of Apoptotic Inhibitors-flipmentioning
confidence: 96%
“…Studies examining the role of cytokines in the pancreatic ␤-cell indicated, by means of mitochondrial depolarization and cytochrome c release, that MPT is a common effector of both apoptosis and necrosis (14,15). Thus, MPT is implicated in ␤-cell death, which is a key factor in the etiology of type 1 diabetes and a potentially important contributor to some forms of type 2 diabetes (16).…”
mentioning
confidence: 99%